(untitled) (KASBIT Business Journal, 2021)
The competitive environment, contemporary world, and the nature of organization have become complex due to which employees want a stable career and life. Having talented employees in the workplace makes the organization competitive and one of the most appropriate strategies is to minimize employee turnover through the career development program. Thus, this study examines employee retention from the perspectives of effective career development. The study collects the input on a self-administrated questionnaire from the employees working in the banking sector of Pakistan. The results of the study reveal that understanding the strategic nature of career development programs link to improve employee attrition. The results of the study also help the managers, practitioners, and HR policymakers to craft effective retention policies and strategies.